Spanish idioms in practice understanding language and culture - Muänoz-Basols, Javier; Pérez Sinusía, Yolanda; David, Marianne (Routledge, 2014)
"From set phrases and idioms to metaphorical expressions and proverbs, these essential components enable users to add humor and spice to their language, vividly embodying Hispanic culture while naturalizing their communication style to more closely resemble that of native speakers." -- Back cover.